Development of English picture vocabulary test as an assessment tool for very young EFL learners’ receptive and expressive language skills - Güngör, Burcu; Önder, Alev (Routledge, 2022)
Research Findings: The aim of this study was to construct and validate “English Picture Vocabulary Test (EPVT)” that aimed to assess the very young learners’ (VYLs) receptive and expressive vocabulary knowledge for specific content areas in English as a foreign language (EFL). In this context, EPVT was created in several stages. One of them was initial construct identification with the literature review on various aspects of assessment in early year’s FL learning and development aspects of very young EFL learners. The other stages were “pre-piloting” with 4 experts and 20 VYLs to obtain their perspectives on the test construction and administration and “final piloting” implementation with 5–6 years old private pre-primary school children (251) to ensure reliability, validity, and test quality. After designing the process of the EPVT was clarified considering the ethical and effectiveness issues, the item analysis with Kuder-Richardson 20 and Point-Biserial Correlation was conducted. Besides, the distribution of the items among the ranges of difficulty and the discrimination index values were specified. Practice and Policy: The findings support that EPVT is child-friendly and effective in assessing preschoolers’ English vocabulary receptively and expressively. Furthermore, it could also serve to provide feedback for teaching and supporting for learning L2.
This study is derived from Burcu Güngör's PhD dissertation and part of it was presented in 6th International Early Childhood Education Congress in Kars, 2–5 October, 2019